A novel photocatalyst CeF3: facile fabrication and photocatalytic performance. Issue 115 (5th November 2015) - Miao, Hui; Huang, Gui-Fang; Xu, Liang; Yang, Yin-Cai; Yang, Ke; Huang, Wei-Qing
Abstract : The synthesized CeF3 nanoparticles can effectively decompose organic contaminants in aqueous solution and show high stability. Abstract : The pursuit of semiconductor photocatalysts with outstanding performance has stimulated increasing efforts to explore novel materials to address problems in environmental remediation and energy utilization. Herein, we first report the synthesis of CeF3 nanoparticles by a facile low-temperature solution combustion method and its performance for photocatalytic degradation of methylene blue (MB) under UV light irradiation. Interestingly, only by adjusting the molar ratios of ammonium fluoride to cerium chloride, pure CeF3 nanoparticles, its mixture with CeO2 and/or Ce2 O3, and pure CeO2 nanoparticles can be easily obtained, respectively. The synthesized CeF3 nanoparticles can effectively decompose organic contaminants in aqueous solution and show enhanced photocatalytic activity than CeO2 nanoparticles. Moreover, CeF3 exhibits high stability. The density functional theory (DFT) calculation has been performed to understand the photocatalysis mechanism of CeF3 nanoparticles. This research might provide some new insights for the synthesis of novel photocatalyst with high photocatalytic performance.